2003
DOI: 10.1007/s00296-003-0389-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic arthropathy caused by Arnold–Chiari malformation with syringomyelia

Abstract: We report a case of neuropathic arthropathy caused by Arnold-Chiari malformation with syringomyelia, with details of the clinical and radiologic aspects. The patient had pain and stiffness in his left upper limb. MRI of the left shoulder revealed neuropathic arthropathy. Upon examination, his left elbow also had the characteristic findings for neuropathic arthropathy. Examination of the spinal cord by MRI confirmed Arnold-Chiari malformation associated with syringomyelia. Neuropathic arthropathy requires evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 6 publications
1
31
0
2
Order By: Relevance
“…Moreover, the arthropathy frequently affects the weight-bearing joints of the body. [1,2,6,10,11] The pathogenesis of Charcot arthropathy has not been clearly definitely as of yet. Its most apparent characteristic is that there is no sensation of pain, but swelling and deformations have also been noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the arthropathy frequently affects the weight-bearing joints of the body. [1,2,6,10,11] The pathogenesis of Charcot arthropathy has not been clearly definitely as of yet. Its most apparent characteristic is that there is no sensation of pain, but swelling and deformations have also been noted.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary bacterial infections may also develop in the same areas, which can cause pathologies such as cellulitis, abscesses, and osteomyelitis. [1,2,6,11,12] The neurovascular theory is another theory, but it is not as popular. It states that sympathetic system regulation in the blood flow of the foot bones is impaired in connection with autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) A standard treatment for neuropathic arthropathy has consisted of conservative measures such as the use of non-weight bearing brace for the immobilization of joints. A study by Hatzis et al 7) have suggested that with regards to the treatment of neuropathic shoulder arthropathy maintaining shoulder joint function takes precedence over fixation through arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Charcot arthropathy is characterized by destruction of the related joint in patients with neurosensory loss.…”
mentioning
confidence: 99%